Implementasi Manajemen Kearsipan Dalam Ketatausahaan di Madrasah Tsanawiyah Darul Ulum Kubu Raya - Jali, M; Amrozi; Hasanuddin; Lukman H; Putri P; Rosiana; Huzaimah; Paras Morgan; Rizka F; A. Ruzi; M. Faisal (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This research was conducted to find out more about the implementation of archives management in administration at Madrasah tsanawiyah Darul ulum Kubu raya by discussing several topics. First, how is the implementation of archives management in administration. Second, what obstacles are faced and efforts to overcome obstacles regarding archive management in administration at madrasah tsanawiyah Darul ulum Kubu raya. The method used in this research is a descriptive method with a qualitative approach. The main data source in this research is the head of administration and staff as an active component in the archive management implementation process obtained through interviews, observation and documentation. Based on the research results, the results of this research are: The implementation of archives management at the madrasah tsanawiyah Darul ulum Kubu raya can be classified in the good category, because it has implemented several indicators regarding archives at the madrasah tsanawiyah Darul ulum Kubu raya, such as recording, distribution, use, maintenance, and deletion of archives, however, as time goes by, it is necessary to always keep abreast of emerging technological developments in order to remain in a good position. Apart from good implementation, of course there are obstacles faced by resolving various obstacles faced in the administration section at madrasah tsanawiyah Darul ulum Kubu raya, such as experiencing difficulty in finding archives that have been stored for a long time, due to the large number of archives that have accumulated. But after being found the archive had been eaten by termites. This is due to inadequate infrastructure. Adding facilities is also hampered by limited space. Several efforts have been made to overcome obstacles in managing archives at the madrasah tsanawiyah Darul ulum Kubu raya, namely copying the archives into computers so that they are not lost and not damaged, in addition to renovating the building, especially the administration room at Madrasah tsanawiyah Darul ulum Kubu raya